2009
DOI: 10.1111/j.1651-2227.2008.01152.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital heart disease in 111 225 births in Belgium: birth prevalence, treatment and survival in the 21st century

Abstract: Survival of congenital heart disease is excellent and continued to improve in the early 21st century. New therapeutic options are increasingly used. This study provides baseline data for the longitudinal follow-up of this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
5
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(141 citation statements)
references
References 30 publications
5
122
5
9
Order By: Relevance
“…A study from Belgium 5 reported an incidence of 8.3% in live and stillborn infants of ≥26 weeks of gestation without chromosome abnormalities. There is likely an even higher incidence in early gestation given spontaneous and elective pregnancy termination.…”
Section: Indications For Referral For Fetal Cardiac Evaluationmentioning
confidence: 99%
“…A study from Belgium 5 reported an incidence of 8.3% in live and stillborn infants of ≥26 weeks of gestation without chromosome abnormalities. There is likely an even higher incidence in early gestation given spontaneous and elective pregnancy termination.…”
Section: Indications For Referral For Fetal Cardiac Evaluationmentioning
confidence: 99%
“…Indeed, perinatal mortality is already as high as 50% in hypoplastic left heart syndrome 22 and is Ϸ40% in univentricular heart. 11 The information obtained in the present study not only is important for estimating survival into adulthood for youngsters with CHD living today but also may be useful for future workforce planning. About a decade ago, Wren and O'Sullivan 23 used the estimated survival data available to calculate the need for follow-up in adult life.…”
Section: Discussionmentioning
confidence: 99%
“…14 Thus, nearly all patients with CHD in Belgium have been evaluated by pediatric cardiology or adult CHD programs, which are all located in university hospitals. On the basis of an epidemiological study comprising 111 225 births in Belgium, 11 we calculated that 27% of all patients with CHD in Belgium are diagnosed, treated, and followed up at the University Hospitals Leuven. Hence, we believe that the results of this study are fairly representative of the population of CHD patients in Western societies.…”
Section: Methodological Issuesmentioning
confidence: 99%
See 2 more Smart Citations